Colleges and schools-College of Agricultural Sciences and Technology-Food Science and Nutrition 001
Dr. Dean Frazeur, chairman of the Csuf Department of Enology, Food Science and Nutrition, prepares to sample a newly developed kiwi sherbet while Juan Garcia, student manager of the university's Dairy Processing Plant, awaits the verdict.